Zur Genese der Thufur Islands und Ost-Grönlands - Schunke, Ekkehard (ERDKUNDE, 1977)
The present study is a survey of the most important results of cryopedological field studies on earth hummocks (thufurs) in Iceland and East Greenland (Angmagssalik) in the years 1970-76. The formation of thufurs is a result of the lateral-horizontal cryostatic pressure, which is caused by differences in the penetration of the freezing front. This locally differential penetrating of the freezing front is initiated by an embryonic hummocky micro-relief of a cellular groundplan. This hummocky micro-relief is caused by the movement of moisture that is adjusted towards the freezing front during the freezing period. The decisive frost-climatic factor is the formation of thufurs and for the relatively uniform shape of thufurs in parts of Iceland and East Greenland, which are different with respect to climate, is a long-term persistence of the freezing front with its adsorption of capillary water in a depth of 20-30 cm. In comparison with materials affected by the formation of thufurs, the spectrum of the grain-size is shifted in facour of the portion of fine and medium-sized sand in those materials, which do not have any thufur formation; moreover, the substrata without any thufurs contain much less organic matter.